STATE REGULATION OF AGRICULTURAL LOGISTICS IN UKRAINE - Fedoruk Ye.I. (Pressing Problems of Public Administration, 2017)
The article is devoted to research about ability to development of ukrainian agri logistics. In articlehave been analyzed the capacity of the domestic agricultural sector and on the basis of resultsgenerated conclusions about the development potential of ukrainian agri logistics.The article systematized number of key instruments for the process of borrowing positive foreignexperience for Ukrainian agri logistics.